Paper Based Glucose Biosensor Depending on SPCE Modified with Hemoglobin and Silver Nanoparticles - Ali Saad Elewi1, Shatha Abdul Wadood1, Abdul Kareem Mohammed Ali1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
In this study, new strategy intended for rapid glucose detection utilizing disposable glucose oxidase (GOD) paper disk integrated with screen-printed carbon electrode (SPCE) modified with hemoglobin (Hb) and silver nanoparticles (AgNPs). The GOD adsorbed on the surface of paper disk and after drying it placed on the surface of the modified SPCE and 16?L of glucose solution were added for the testing. Different parameters such as applied potential, concentration of enzyme, pH, size of paper disk, and the volume of buffer were optimized to improve the efficiency of this glucose biosensor.